Dinamika Psikologis Mahasiswa Jurusan Seni Tari ISI Padang Panjang dalam Menentukan Bentuk Tugas Akhir - Aisyah Putri Mersi; Kurniadi Ilham; A.A.I.A Citrawati; Nurmalena Nurmalena (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the psychological dynamics of students of the Dance Arts Department of ISI Padangpanjang in determining the form of their final assignment between dance creation and dance study. The study used a qualitative method with a phenomenological approach. Data were obtained through observation, interviews, and documentation of 14 active students from the 2022-2024 intake and two supporting informants. Data analysis was carried out through data reduction, identification of important statements, grouping themes, data presentation, and drawing conclusions. The results showed that students experienced various psychological dynamics such as confusion, doubt, inner conflict between interests and abilities, anxiety, and dilemmas in determining the choice of their final assignment. Factors influencing these conditions include motivation, academic experience, psychological condition, social environment, and financial factors. Support from lecturers, friends, and seniors had both positive and negative influences on the decision-making process. This study concluded that determining the form of the final assignment is not only an academic decision, but also a psychological process influenced by internal and external factors of the students.